Cidade fragmentada: os usos das redes elétricas em favelas do município de Vitória-ES - Zanotelli, Cláudio; Lacerda, Lucas do Carmo Falcão de; Galvão, Victor Araújo (Geografares, 2020)
DOI: 10.7147/GEO6.1020